INTERVENTION OF THE HEALTHY LIVING COMMUNITY MOVEMENT (GERMAS) ON THE ELDERLY AT UPTD RUMOH SEUJAHTERA GEUNASEH SAYANG ULEE KARENG DISTRICT, BANDA ACEH CITY - Saputra, Fitra Jaya; Basri, Suzanna Hasan; Ramadhaniah, Ramadhaniah; Zakaria, Radhiah (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2025)
Background: The Healthy Living Community Movement (GERMAS) is one of the efforts to increase the awareness, willingness, and ability of every individual, especially the elderly, to live a healthy life to improve the highest degree of public health. This study aims to see the difference in the knowledge of Germas before and after intervention in the elderly at UPTD Rumoh Seujahtera Geunaseh Sayang Ulee Kareng District, Banda Aceh in 2019. Method: This research was carried out using a descriptive analytical method with an Experimental Quasi (pseudo) design. The population in this study is the elderly who live in UPTD Rumoh Seujahtera Geunaseh Sayang, Ulee Kareng District, Banda Aceh City. The respondents in this study were 37 elderly people. Data collection was carried out for 3 days from 24 to 26 January 2019 using a guided interview. Data analysis was conducted using a paired sample test with the SPSS 16.0 program. Result: The results of the study showed that there were differences before and after the counselling intervention on Germas in the elderly at UPTD Rumoh Seujahtera Geunaseh Sayang Ulee Kareng District, Banda Aceh City in 2019 with a p value of 0.006. There were differences in knowledge about Physical Activity (p value 0.000), early detection of disease (p value 0.037), and healthy and nutritious food (p value 0.037) before and after the intervention. Recommendation: It is expected that parties related to the management of UPTD Rumoh Seujahtera Geunaseh Sayang Ulee Kareng District, Banda Aceh will be able to ensure that counselling and coaching activities about the importance of the Healthy Living Community Movement for the Elderly are carried out routinely at least 1-3 times a month.